Beneath the Texas sky [large type] - Thomas, Jodi (Thorndike Press large print core, 2011)
"Texas Ranger Josh Weston is a complete stranger to Bethanie Lane, and her only chance to escape from her uncle's grasp. Without hesitating, she strikes a deal with the rugged lawman to take her with him when he leaves San Antonio. And on the journey to his family's ranch near Fort Worth, they forge a bond as powerful as it is unexpected. When Bethanie's dream of a future with Josh falls apart, she's forced to make a harrowing choice. Yet through every danger and revelation, one thing remains: a love worth living and dying for."-- Provided by publisher.